Analysis of Teaching Strategy of Computer Data Audit Course based on Learning Problems (Contemporary Education and Teaching Research, 2022)
The rapid reform of audit informatization means that the traditional teaching methods can no longer meet the current changeable audit methods and audit environment, which indicates that the computer data audit course in colleges and universities needs to keep pace with the times and cultivate high-quality talents with practical initiative. Applying the problem-based learning teaching method to the teaching of computer data audit course can help students improve their thinking ability and enable them to adapt quickly to the changeable audit work environment. This paper is the author's analysis of the application strategy of problem-based learning teaching method in the teaching of computer data audit course, based on the actual teaching experience.